TRANSFORMATION OF BEHAVIORAL ARCHITECTURE: SPATIAL AND PSYCHOLOGICAL STRATEGIES IN DESIGNING A SOCIAL CENTER FOR STREET CHILDREN IN MEDAN CITY - Putri Wadda Nabila; Hajar Suwantoro (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The urban development of Medan, Indonesia, reflects a growing social challenge related to the presence of street children living in vulnerable conditions. Official data from the Social Service of North Sumatra indicate that there are approximately 525 street children. Current social facilities often adopt a warehousing model, referring to large scale, institutionalized mass shelter systems that tend to neglect the psychological needs of users. This is particularly concerning given that 92% of street children suffer from profound trauma. This study proposes a Trauma-Informed Healing Architecture (TIHA) framework for a Social Center in Medan Selayang. By synthesizing Irwin Altman’s Territoriality and J. Douglas Porteous’s "Meaning of Home," the research identifies spatial strategies to mitigate triggers and foster recovery. Methodologically, a qualitative descriptive approach is used to analyze local demographic data against global benchmarks. Key findings suggest that circular massing for passive surveillance, zonal acoustic buffering to counter traffic noise, and the provision of primary territories significantly reduce aggression. The resulting design integrates neo-vernacular stilt architecture to address urban flooding while restoring the dignity and agency of marginalized youth.